La dimension atlantique des révolutions hispano-américaines - Federica Morelli (Les Cahiers de Framespa)
This essay examines the different interpretations historians have attributed to Hispanic American revolutions over time. The relevance of an Atlantic reading of these processes, which has recently emerged, is founded, on the one hand, on the comparability of American societies and dynamics from the Seven Years’ War to the formation of national states, and, on the other, on the existence of transatlantic cultural transfers during the age of revolutions.